Efektivitas Model Latihan Jump to Box dan Double Leg Cone Hop terhadap Peningkatan Akurasi Heading - Suwita, Yossa (Unnes Journal of Sport Sciences, 2021)
Jump to box and double leg cone hop exercises are forms of plyometric training. Theformulation of the research problem is whether there is an effect of jump to box exercise anddouble leg cone hop exercise on heading and which is the most effective of the twoexercises. This study aims to determine the effect of the two plyometric exercises and themost effective results of the two plyometric exercises on heading accuracy. This study usesan experimental method using a quantitative approach. The population of this study wereall players of SSB Salatiga FC, so the number of research samples were 20 players. Thefindings showed that the effect of jump to box exercise was more effective than double legcone hop exercise on increasing heading accuracy applied to SSB Salatiga FC KU players16-18 years old. The conclusion indicated that jump to box exercise is more effective thanthe double leg cone hop exercise. For the suggestion, soccer players can apply jump to boxexercises to improve the heading accuracy.